Visual Displays that Directly Interface and Provide Read‐Outs of Molecular States via Molecular Graphics Processing Units1. (9th July 2014) - Poje, Julia E.; Kastratovic, Tamara; Macdonald, Andrew R.; Guillermo, Ana C.; Troetti, Steven E.; Jabado, Omar J.; Fanning, M. Leigh; Stefanovic, Darko; Macdonald, Joanne
Abstract The monitoring of molecular systems usually requires sophisticated technologies to interpret nanoscale events into electronic‐decipherable signals. We demonstrate a new method for obtaining read‐outs of molecular states that uses graphics processing units made from molecular circuits. Because they are made from molecules, the units are able to directly interact with molecular systems. We developed deoxyribozyme‐based graphics processing units able to monitor nucleic acids and output alphanumerical read‐outs via a fluorescent display. Using this design we created a molecular 7‐segment display, a molecular calculator able to add and multiply small numbers, and a molecular automaton able to diagnose Ebola and Marburg virus sequences. These molecular graphics processing units provide insight for the construction of autonomous biosensing devices, and are essential components for the development of molecular computing platforms devoid of electronics.